2018
DOI: 10.3390/su10082800
|View full text |Cite
|
Sign up to set email alerts
|

A Framework for Spatiotemporal Analysis of Regional Economic Agglomeration Patterns

Abstract: Understanding regional economic agglomeration patterns is critical for sustainable economic development, urban planning and proper utilization of regional resources. Taking Guangdong Province of China as the study area, this paper introduces a comprehensive research framework for analyzing regional economic agglomeration patterns and understanding their spatiotemporal characteristics. First, convergence and autocorrelation methods are applied to understand the economic spatial patterns. Then, the intercity spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 50 publications
(49 reference statements)
0
3
0
Order By: Relevance
“…Moreover, interactions between regions or cities are mainly reflected by the agglomeration and diffusion of various factors, which are the driving force for the evolution of regional spatial structure [21]. Jin et al (2018) [22] argued that understanding regional economic agglomeration patterns is critical for sustainable economic development, urban planning and proper utilization of regional resources. As such, the urban energy level from the view of fields can be treated as a special kind of "external economic connection level" and reflects a city's interaction with other cities, which is of great significance to the sustainable development of regional economy, the evolution of regional spatial structure and urban planning.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moreover, interactions between regions or cities are mainly reflected by the agglomeration and diffusion of various factors, which are the driving force for the evolution of regional spatial structure [21]. Jin et al (2018) [22] argued that understanding regional economic agglomeration patterns is critical for sustainable economic development, urban planning and proper utilization of regional resources. As such, the urban energy level from the view of fields can be treated as a special kind of "external economic connection level" and reflects a city's interaction with other cities, which is of great significance to the sustainable development of regional economy, the evolution of regional spatial structure and urban planning.…”
Section: Literature Reviewmentioning
confidence: 99%
“…With the spatial agglomeration of economic activities, population and resources are gradually gathered in regions with economic prosperity, causing an imbalanced spatial pattern of regional economy, population, resources, and infrastructure. Many studies have demonstrated that an inverted-U relationship exists between agglomeration and the economy [8]. Agglomeration can greatly promote regional development in early stages while leading to a decline in the regional economy after the agglomeration exceeds the limits.…”
Section: Theoretical Basismentioning
confidence: 99%
“…Following the principle that "understanding urban space requires understanding flows and networks" [37], the study of urban interactions from the perspective of flow space has gradually become mainstream. With urban nodes as the unit of analysis, flow space research emphasizes the relational and connected nature of urban space [38], focusing on the analysis of network structures [39] from the perspectives of regional economies [40], tourism flows [41], population flows [42], traffic flows [43], and commuting flows [44], thus validating the flexibility and superiority of flow space for portraying urban linkages. In the meantime, with its impartiality and precision, community detection has become an innovative trend in the research of urban spatial networks [45], and it has been tentatively utilized in the evolution of urban structure [46] and the identification of spatial boundaries.…”
Section: Introductionmentioning
confidence: 99%